Innovation in Economic Learning Through Digital Simulations and Educational Games - Abdillah; Mashuri Toha; Abd. Qadir jailani; Yusfar Ramadhan (Penerbit Hellow Pustaka, 2025)
The development of digital technology and Artificial Intelligence (AI) has transformed educational paradigms, including in the field of economics education. This article aims to examine how digital transformation affects economics learning at the secondary school level and to analyze implementation strategies that are relevant to 21st-century needs. The study employs a qualitative method with a literature review approach by analyzing various scholarly sources, educational policy reports, and recent research findings. The results indicate that the integration of digital technology in economics education can enhance learning motivation, broaden access to learning resources, and strengthen students’ economic literacy. The use of digital platforms such as Learning Management Systems (LMS), virtual market simulations, and interactive financial applications has proven effective in supporting contextual learning. Nevertheless, several challenges remain, including limited infrastructure, low levels of teachers’ digital literacy, and a lack of professional training, which hinder the optimal implementation of technology-based learning. The study concludes that digital transformation is an imperative in modern economics education. Successful implementation requires adaptive educational policies, improved teacher competencies, and the development of innovative technology-based learning media integrated with entrepreneurial values. These findings are expected to serve as a reference for educators and policymakers in designing economics education strategies that are relevant to the demands of the digital era.